Faktor Faktor-Faktor yang Mempengaruhi Kinerja Auditor Pemerintah di Inspektorat Daerah CIAYUMAJAKUNING - Sumantri Hanif Wardana; Nova Firdausi; Ida Rosnidah; Salta (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2025)
This study aims to analyze the influence of competence, independence, professionalism, skepticism, and professional ethics on auditor performance at the Ciayumajakuning Regional Inspectorate. Using a census method, the study involved the entire population of 159 auditors in the regions of Cirebon, Indramayu, Majalengka, Kuningan, and Cirebon City. Data were obtained through a structured questionnaire and analyzed using multiple linear regression to examine both the simultaneous and partial effects of each independent variable on auditor performance. The results show that all five variables significantly affect auditor performance, with professionalism having the greatest influence, followed by competence, professional ethics, independence, and skepticism. The inclusion of skepticism and professional ethics distinguishes this study, expanding the understanding of relationships among variables in the context of public sector auditing. These findings provide practical implications for the Regional Inspectorate to improve audit quality through continuous training, integrity building, and code of ethics reinforcement, and for local governments in formulating strategic policies and providing competent, professional, high-integrity human resources.